Live‐Cell Localization Microscopy with a Fluorogenic and Self‐Blinking Tetrazine Probe - Werther, Philipp (Angew Chem Int Ed Engl, 2019)
Recent developments in fluorescence microscopy call for novel small‐molecule‐based labels with multiple functionalities to satisfy different experimental requirements. A current limitation in the advancement of live‐cell single‐molecule localization microscopy is the high excitation power required to induce blinking. This is in marked contrast to the minimal phototoxicity required in live‐cell experiments. At the same time, quality of super‐resolution imaging depends on high label specificity, making removal of excess dye essential. Approaching both hurdles, we present the design and synthesis of a small‐molecule label comprising both fluorogenic and self‐blinking features. Bioorthogonal click chemistry ensures fast and highly selective attachment onto a variety of biomolecular targets. Along with spectroscopic characterization, we demonstrate that the probe improves quality and conditions for regular and single‐molecule localization microscopy on live‐cell samples.